The more moderate side of Joseph de Maistre : views on political liberty and political economy - Camcastle, Cara, 1973- (McGill-Queen's studies in the history of ideas ;, 2005)
"The More Moderate Side of Joseph de Maistre expertly contextualizes the work of de Maistre within the historical events and intellectual debates that emerged in the aftermath of the French Revolution. Camcastle sheds new light on Maistre's conception of government as being made up of groups in dynamic counterbalance and on the system of inconvertible paper money that he developed a century before a similar system was universally adopted in the twentieth century. Camcastle provides a more complete and balanced picture of Maistre's political writings through original interpretations of his published works and translations from French and Italian into English of previously unpublished writings that substantiate key points."--Jacket.